Public awareness and knowledge about Shariah-compliant investment: a survey on Putrajaya residents / Muhammad Zulhafiz Taqiyuddin - Taqiyuddin, Muhammad Zulhafiz (2022)
Lack of data and not knowing the level of public awareness and understanding of the basics of Islamic investment that has been applied in the Islamic banking and financial system in Malaysia are issues and concerns that need to be highlighted. There is an urgent need to increase the awareness and understanding of the Bumiputera Muslim community so that they can know the basics and principles of investment practiced in the Malaysian Islamic capital market. Therefore, a questionnaire approach is needed to test and measure the level of awareness and understanding of the Muslim community on the issues raised in order to be guided by the Malaysian government as the hub of Islamic finance in Malaysia. This study aims to examine the basic understanding of the Muslim community which is a factor in the issue of lack of appreciation of Muslims in Malaysia towards Shariah-compliant investments. This study was specifically conducted in the district of the Federal Territory, Putrajaya as an administrative state inhabited almost entirely by Bumiputera Muslim. The data obtained for this study were obtained through a survey questionnaire distributed to local residents in the Federal Territory, Putrajaya. In addition, the data obtained were analyzed using the quantitative analysis method where each variable is measured with a reliability test to obtain the alpha value accepted as a variable. to assess and determine the level of awareness and understanding that influences the issues that arise among Muslims today. The results of a study conducted on respondents in the Federal Territory, Putrajaya found that the level of awareness and understanding of the Muslim community in the district is at a good level but a concern is that the selection of Shariah-compliant investment products and services is still not a comprehensive and final choice among respondents. It is hoped that this study can contribute to the improvement of awareness and understanding of the importance of knowing the basics and principles of Shariahcompliant investments that have developed over the decades in Malaysia.